Relevance of Selected Training Principles in the Field of Exercise and Fracture Prevention Stellenwert ausgewählter Trainingsprinzipien innerhalb eines körperlichen Trainings zur Frakturprophylaxe - Von Stengel, Simon; Kohl, Matthias; Jakob, Franz; Kerschan-Schindl, Katharina; Lange, Uwe; Peters, Stefan; Thomasius, Friederike; Uder, Michael; Fröhlich, Michael; Schöne, Daniel; Kemmler, Wolfgang; Shojaa, Mahdieh (Osteologie, 2023)
Training principles are regarded as specific guidelines for physical exercise training and cover all superordinate aspects of training, largely independent of the addressed outcome. Relevant for non-athletic exercise are primarily principles for triggering and maintaining adaptation. While the overload principle and the principle of progressive overload i. e. systematically triggering and maintaining training demands over the system-specific threshold are predominately considered in exercise protocols in the field of exercise and fracture prevention, training principles related to specificity, individualization and variation are frequently not addressed with the necessary emphasis. In particular, the principle of specificity, i. e. the aspect that adaptation is specific to the applied stimulus und hence transfer effects between even closely related systems cannot necessarily be expected is a critical issue particularly in the area of balance exercise. In parallel, the individualization of the training protocol has to consider not only exercise specific issues, but also time and transfer aspects, functional limitations, pain, as well as individual predispositions. Another critical aspect of many training programs is exercise continuity. There is considerable evidence that even detraining periods as short as 4-6 weeks trigger significant and clinically relevant reductions in parameters related to fracture reduction. Finally, we advocate the introduction of recognized athletic training principles associated to periodization in order to structure the trainings process more clearly and to allow greater focus on dedicated training aims. In summary, the proper consideration and careful transfer of training principles is an essential component of successful training protocols in the area of fracture prevention. Unfortunately, many exercise training protocols demonstrate considerable deficits in this area.
CRIS-Team Scopus Importer:2023-09-22
Keywords: bone strength; exercise recommendations; falls; fracture prevention; training principles